RELATIONSHIP BETWEEN QUALITY ASSURANCE OFFICERS' TRAINING AND CUSTOMER SATISFACTION IN PUBLIC UNIVERSITIES IN KENYA - Boiyon, Edward Kiplangat; Manduku, Joshua; Rotumoi, Joseph (African Journal of Education and Practice, 2020)
Purpose: The purpose of the study was to investigate the relationship between Quality Assurance Officers' training and Customer Satisfaction in Public Universities in Kenya. Methodology: The researcher employed Correlation research design using mixed methods approach. This study was undertaken in public universities in Kenya. There were 31 public universities in Kenya. These universities are spread across the country. Out of these, 15 had been awarded ISO 9001 QMS certification (Kenya Bureau of Standards, 2019). A sample of 8 universities was used for the study. All universities are regulated by CUE hence the same standards ought to apply in regard QMS. Data was analyzed using both descriptive statistics such as frequencies, mean, mode, median and inferential statistics such as linear regression. Data was presented using tables and figures. Findings: The study shows a weak relationship exist between QAOs training and customer satisfaction (Î² =0.210). The relationship was not significant at 95% level of significance (P-value=<0.050). This finding implied that an improvement in training of QAOs by one unit led to a 0.210-unit improvement in customer satisfaction. There is a need to improve quality of training offered to quality assurance officers alongside ISO standards Unique contribution to theory, practice and policy: The results of this research will inform both the public universities and the Ministry of Education in Kenya so that they may appreciate the gaps in quality of training of staffs so as to enhance customer satisfaction. Universities management may also benefit from the results of the study because it may expose the gaps in training and preparation of QAOs in execution of their mandate/duties. Organizations receive ISO 9001 certification that specifies the requirements for a quality management system where an organization needs to demonstrate its ability to consistently produce quality products and services. ISO 9001 certification also aims to enhance the quality of services through effective application of the system continual improvement, the assurance of conformity to customers and applicable statutory and regulatory requirements. Furthermore, the findings of this study may generate useful theoretical literature for further studies and the necessary actions that will be undertaken in order to address the issue of quality services in our public universities.